Effects of varying creep feeding duration on proportion of pigs consuming creep feed and pre-weaning performance - Sulabo, R.C.; Wiedemann, E.J.; Jacela, J.Y.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 54 sows (PIC Line 1050) and their litters were used in this study to determine the effects of varying durations of creep feeding on the rate of pigs consuming creep feed (eaters) and pre-weaning performance. Two groups of sows were blocked according to parity and date of farrowing and allotted to three experimental treatments using a randomized complete block design. Creep feeding was initiated at d 7, 14, and 18 from birth for a duration of 13, 6, and 2 d of creep feeding. A creep diet (1,585 kcal ME/lb, 1.56% TID Lys) with 1.0% chromium oxide was offered ad libitum until weaning (d 20) using a rotary creep feeder with hopper. A single lactation diet (1,586 kcal ME/lb, 0.97% TID Lys) was used where sows were allowed free access to feed throughout lactation. Piglets were weighed individually at d 0 (birth), 7, 14, 18, and 20 to calculate total and daily gains. Daily creep feed intake per litter was recorded and calculated. Fecal samples from all piglets were taken twice per sampling day using sterile swabs at d 14, 18, and 20 for Treatment 1; at d 18 and 20 for Treatment 2; and d 20 for Treatment 3. Piglets were categorized as ‘eaters’ when fecal sample was colored green at least once on any of the sampling days. Overall, there were no differences in weaning weights (P<0.61), total gain (P<0.38), and daily gain (P<0.38) among pigs and litters fed creep for different durations. Total creep feed intake of litters fed creep for 13 and 6 d were greater (P<0.0001) than those litters provided creep feed for 2 d. There were no differences (P<0.69) in overall creep intake between litters fed for 13 and 6 d. Litters provided with creep feed for 13 d produced 10% more (80 vs. 70%; P<0.03) eaters than litters fed creep for both 6 and 2 d. There were no differences (P<0.98) in the percentage of eaters between litters fed creep for 6 and 2 d. In conclusion, longer durations of creep feeding did not affect pre-weaning gain and weaning weights but did increase the proportion of eaters in whole litters; however, a relatively high percentage of pigs (70%) were classified as eaters by providing creep feed for only 2 d prior to weaning.
Keywords: Swine; Feed management; Creep feeding; feeding duration